2012
DOI: 10.1186/alzrt118
|View full text |Cite
|
Sign up to set email alerts
|

Whether, when and how chronic inflammation increases the risk of developing late-onset Alzheimer's disease

Abstract: Neuropathological studies have revealed the presence of a broad variety of inflammation-related proteins (complement factors, acute-phase proteins, pro-inflammatory cytokines) in Alzheimer's disease (AD) brains. These constituents of innate immunity are involved in several crucial pathogenic events of the underlying pathological cascade in AD, and recent studies have shown that innate immunity is involved in the etiology of late-onset AD. Genome-wide association studies have demonstrated gene loci that are lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 82 publications
1
61
0
Order By: Relevance
“…According to the previous study, both erythrocyte and lysosomal membrane have a similar molecular composition, hence, any agent that could stabilize the red blood cell membrane from hemolysis would provide a good insight into the anti-inflammatory mechanism of action [21]. More so, epidemiological and experimental studies have suggested an association between acute and chronic inflammation and risk of developing numerous pathological disorders [23,24]. Hence, natural compounds from plants that mitigate against inflammation could serve as therapy in the management of inflammation-mediated disorders.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous study, both erythrocyte and lysosomal membrane have a similar molecular composition, hence, any agent that could stabilize the red blood cell membrane from hemolysis would provide a good insight into the anti-inflammatory mechanism of action [21]. More so, epidemiological and experimental studies have suggested an association between acute and chronic inflammation and risk of developing numerous pathological disorders [23,24]. Hence, natural compounds from plants that mitigate against inflammation could serve as therapy in the management of inflammation-mediated disorders.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Systemic inflammation can increase cytokine expression in the brain and initiate amyloid deposition via activation of microglial cells and amyloid-associated proteins. 29,77 We have demonstrated that the expression of SAA1 in the liver after brain injury did not result in the formation of detectable amyloid species. Because SAA1 levels decreased significantly by 3 dpi, presumably persistent accumulation of SAA1 for a longer time period is needed to initiate amyloid formation.…”
Section: Influence Of the Liver On The Brain's Response To Injurymentioning
confidence: 99%
“…Several prospective epidemiological studies have found that increased acute phase mediator serum levels can serve as a risk factor for AD, as detailed in a review article by Eikelenboom et al 78 In addition, other clinical studies compiled in the review have suggested that increased peripheral inflammation is associated with a greater risk of dementia, mainly in patients with pre-existing cognitive impairments, and accelerates subsequent deterioration in patients with dementia. 78 Higher levels of serum C-reactive protein (CRP) in middle-aged patients are also associated with an increased risk of AD and vascular dementia, which may indicate that inflammatory factors are a reflection of both dementia-related peripheral disease and cerebral mechanisms.…”
Section: F U N C T I O N O F a C U T E P H A S E P R O T E I N Smentioning
confidence: 99%
“…78 Higher levels of serum C-reactive protein (CRP) in middle-aged patients are also associated with an increased risk of AD and vascular dementia, which may indicate that inflammatory factors are a reflection of both dementia-related peripheral disease and cerebral mechanisms. 78 Of note is the fact that these processes can be measured long before manifestations of dementia begin to be observed. Follow-up studies in the elderly have also revealed a correlation between serum CRP levels and an increased incidence of dementia and AD.…”
Section: F U N C T I O N O F a C U T E P H A S E P R O T E I N Smentioning
confidence: 99%